Crowd-sourcing higher education architecting the sustainable design and development of E-Learning in Africa - Griff Richards (Открытое образование (Москва), 2016)
Post-secondary access in Africa hovers around 6%, in part because there is a lack of access to physical campuses. In Phase I of the African Virtual University’s Multinational Project, 73 undergraduate courses were developed and published as OERs in English, French and Portuguese. These in turn were adopted and localized by African universities. While over 1.3 million downloads of the materials have taken place in the last 5 years, no attempt was made to harness the input of user to maintain or improve the courses. Seven years later, the African Virtual University will renew these courses along with another 50 or so in disciplines of high demand. But this time the AVU architecture will call for a sustainable approach to e-learning that challenges the 22 universities in 15 countries to not only help further develop the courses, but also to maintain them and sustain them across multiple languages.This article discusses the potential role of crowd-sourcing in curriculum development, and sketches a preliminary architecture for building a community of practice to sustain e-Learning in Africa.